2020
DOI: 10.21608/jacb.2020.95837
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals, Antioxidant Activity and Identification of Phenolic Compounds by HPLC of Pomegranate (Punica granatum L.) Peel Extracts

Abstract: Pomegranate peel is food waste unfit to eat parts obtained during the production of pomegranate juice. The aim of this work is to study the effect of four different solvents (ethanol, isopropanol, hot and cold water) on phytochemicals screening, total phenolics content, total flavonoid content and antioxidants activity in pomegranate peels, as well as identification of phenolic compounds in extracts by HPLC. Phenolics, flavonoids, alkaloids, saponins, tannins, steroids and terpenoids were detected in all extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…The most abundant antioxidant and antimicrobial compound found was p-coumaric acid with a concentration of 256.7 ± 6.8 g/100 g of DE followed by ferulic acid 168.4 ± 1.8 g/100 g of DE. The results were in agreement with previous reports by [ 47 , 48 ], who reported the abundance of p-coumaric acid in plant extracts. The identification of phytochemicals indicates that antioxidant and other biological properties of extract could be due to the presence of these bioactive compounds.…”
Section: Resultssupporting
confidence: 94%
“…The most abundant antioxidant and antimicrobial compound found was p-coumaric acid with a concentration of 256.7 ± 6.8 g/100 g of DE followed by ferulic acid 168.4 ± 1.8 g/100 g of DE. The results were in agreement with previous reports by [ 47 , 48 ], who reported the abundance of p-coumaric acid in plant extracts. The identification of phytochemicals indicates that antioxidant and other biological properties of extract could be due to the presence of these bioactive compounds.…”
Section: Resultssupporting
confidence: 94%
“…Gallo tannins, ellagic acid, punicalins, punicalagins, and gallic acid are some of the major phytochemicals present in pomegranate peel, as shown in Figure 1 . 15 El-Hamamsy and El-khamissi 16 revealed that pomegranate peel extract (PPE) is rich in several phytochemicals, including tannins, steroids, phenolics, alkaloids, flavonoids, terpenoids, and saponins. Nine polyphenolic constituents, including p -coumaric acid, syringic acid, benzoic acid, ellagic acid, caffeic acid, cinnamic acid, protocatechuic acid, isoferulic acid, and quinic acid, were identified and quantified in the extracts using HPLC.…”
Section: Pomegranate Peel Phytochemistrymentioning
confidence: 99%
“…Every day, PoPs are used in various food varieties owing to their great nutritional and chemical composition (Kandylis & Kokkinomagoulos, 2020 ). PoP contains high levels of carbohydrates (59.60%) followed by moisture content (5.40%–5.95%), protein content (4.90%–8.97%), ash content (3.40%–4.22%), fiber content (16.30%–19.41%), and fat content (0.85%–1.26%) (El‐Hamamsy & El‐khamissi, 2020 ; Khan et al, 2017 ). The chemical and nutritional composition of PoP were presented in Table 1 .…”
Section: Introductionmentioning
confidence: 99%